Isolation of Peroxidase enzyme from various vegetables and coupling to IgG - Hemalatha, P.; Shivani, K.; Godavari, M.; Vidhya, T. Sri; Devi, S. Manju; Padma, A. Sai (Nepal Journal of Science and Technology, 2023)
Coupling of IgG with peroxidase enzyme finds various applications in determining the antigen-antibody interactions, in diagnostics or for research purpose. In the present study, Peroxidase enzyme was isolated from various vegetables like tomato (Solanum lycopersicum), cabbage (Brassica oleracea) and Radish (Raphanus sativus) and partial purification of enzymes was done with ammonium sulphate fractionation to 80% saturation. The active peroxidase enzyme was coupled to Goat anti-human IgG and the efficiency of coupling procedure was tested against Protein A sepharose purified human IgG. The coupling procedure was done by using sodium periodate and coupling was confirmed by dot blot and ELISA procedures. The present study provides an indigenous method to isolate an active peroxidase enzyme and couple to various IgG and use in immuno detection methods at very cost effective manner.